Analisis Strategi Promosi Pinjaman Tanpa Bunga dalam Mendorong Pertumbuhan UMKM pada Bank Wakaf Mikro Alpen Barokah Mandiri - Uswatun Hasanah Sudir; Cici’ Insiyah (Universitas Muhammadiyah Surabaya, 2026)
The research problem addressed in this study is divided into two main areas: how the provision of interest-free loans by the Alpen Barokah Al-Amien Prenduan Micro Waqf Bank can encourage the growth of MSMEs around the Al-Amien Prenduan Islamic Boarding School and how the promotional strategies implemented by the Alpen Barokah Al-Amien Prenduan Micro Waqf Bank can encourage the growth of MSMEs around the Al-Amien Prenduan Islamic Boarding School. This study used a qualitative approach with data collection methods including interviews, observation, and documentation. The data obtained were analyzed using data reduction, data presentation, and conclusion drawing techniques. The focus of this study was to understand the marketing strategies implemented by BWM and their impact on customer business development. The results showed that the promotional strategies implemented by BWM Alpen Barokah Mandiri were quite effective in raising public awareness of the importance of Sharia-based financing. These strategies included a community approach through group religious study and training (HALMI). utilization of social media, and partnerships with community leaders. Furthermore, the interest-free loans provided by BWM have been shown to have a positive impact on MSME growth, both in terms of increased turnover and business sustainability. This study recommends increasing innovative promotional strategies to enable more MSMEs to utilize this Sharia financing facility.